PENGARUH BUDAYA KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PELAYANAN PDAM TIRTA MUSI PALEMBANG UNIT RAMBUTAN - M. Anton Septadi; Zunaidah Zunaidah (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2014)
PDAM Tirta Musi Palembang is one of firms own by local state entrusted to manage water supply in the surrounding area. This firm used work culture environment to do their activities, heightening their sense of productivity aligns with firm’s goal: to ensure society’s development regarding social aspect, economy, health, and civil service. This research is entitled to understand effects of those work culture environment with worker’s productivity in PDAM Tirta Musi Palembang Unit Rambutan. In this research, researcher used library research, questioner, and observation as instrument to collect data. After all those primary data collected, then researcher calculated data using Statistical program SPSS Version 16.0. Testing used in this research is data validation testing; reliability validation; and normality validation. This research yielding results that work culture environment have significant effect in worker’s productivity. On the other hand, productivity not only effected by work culture, but also by motivations; compensations; leadership; and other factors. In this opportunity, researcher would also suggest to firm and related to do further research to understand other factors that can also effect worker’s productivity.Keywords: Work Culture and Worker’s Productivity